INOVASI DIGITAL DALAM PERENCANAAN PENDIDIKAN ISLAM DI STAI AL-AZHARY CIANJUR: STUDI KASUS INTEGRASI SIMAK DAN PEMBELAJARAN SINKRON - Adriati Mariyam, Vivi; Safwandy Nugraha, Mulyawan (Epistemic: Jurnal Ilmiah Pendidikan, 2026)
Digital transformation has become a strategic agenda in Islamic education management, particularly in Islamic religious universities facing technological adaptation challenges. This study analyzes digital innovation in Islamic education planning, focusing on how the integration of Academic Information Systems (SIMAK) and synchronous learning platforms such as Zoom and Google Meet enhances access, coordination, and learning effectiveness. The research adopts a qualitative case study approach, using in-depth interviews with institutional leaders, lecturers, and students, complemented by academic planning document reviews. The study contributes a conceptual model of digital planning in Islamic education, identifying key barriers such as access issues and digital competency gaps, and offers strategic recommendations for institutions to improve digital education governance. Findings reveal that SIMAK serves as the backbone of academic administration and scheduling, while Zoom and Google Meet support synchronous learning. However, uneven internet access and varying digital competence among lecturers remain significant obstacles. The proposed model integrates technology with Islamic values to create adaptive, just, and sustainable digital governance in Islamic higher education.